PENGARUH KREDIBILITAS BRAND AMBASSADOR DAN TERPAAN PROMOSI PENJUALAN PRODUK FASHION DI SHOPEE TERHADAP IMPULSIVE BUYING GENERASI Z PADA ERIGO DI SHOPEE - Putra Aditya, Yudha; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
This study aims to examine the influence of brand ambassador credibility and sales promotion exposure on impulse purchases of Erigo products on Shopee by Generation Z, using the Source Credibility Theory and CIFE Model. Using a quantitative method with 100 respondents, the results show that brand ambassador credibility contributes 76.2% (coefficient 0.803) and sales promotion exposure 64% (coefficient 1.764) to impulse buying. The higher the credibility of the brand ambassador and exposure to sales promotions, the higher the impulse buying behavior. Both variables are proven to influence impulse purchases of Erigo products on Shopee by Generation Z. This study recommends further research to investigate other variables that influence impulse buying.